Effect of fly ash on the corrosion performance and structural integrity of stainless steel concrete rebars in acid rain and saline environments (Fracture and Structural Integrity, 2019)
The corrosion behavior of 304L stainless steel rebars in an alkaline solution simulating new concrete subjected to acid rain attack and a mildly to slightly acidic solution simulating corroded cover concrete that exposed the reinforcement to direct acid rain attack, was investigated by reverse polarization. Both solutions contained Ca(OH)2 and fly ash (0-25 wt.% of the dry mixture). Concrete cubes containing 0-25 wt.% fly ash and reinforced with 304L rebars were subjected to salt spraying for 4 m. Although the polarization behaviors in the two electrolytes were different, the relative trends with respect to the fly ash contents were similar. The beneficial effect of fly ash (up to 20 wt.%) on the corrosion resistance of 304L rebars was demonstrated. However, a deteriorating effect was realized at 25 wt.% addition. Partial replacement of cement by fly ash did not significantly affect the tensile properties of the 304L rebar before or after 4 m of salt spraying. The elastic modulus and percent elongation presented a slight decrease after 4 m of salt spraying, irrespectively of FA content. Corrosion-wise, 304L can replace 316L stainless steel provided that FA has been added to the concrete mixture, even at low contents (10 or 15 wt.%).
Keywords: 304L rebars; Fly ash; Acid rain; Reverse polarization; Salt spraying; Tensile properties